Myocardial viability of the peri-infarct region measured by T1 mapping post manganese-enhanced MRI correlates with LV dysfunction. (15th April 2019) - Tada, Yuko; Heidary, Shahriar; Tachibana, Atsushi; Zaman, Junaid; Neofytou, Evgenios; Dash, Rajesh; Wu, Joseph C.; Yang, Phillip C.
Abstract: Background: Manganese-enhanced MRI (MEMRI) detects viable cardiomyocytes based on the intracellular manganese uptake via L-type calcium-channels. This study aimed to quantify myocardial viability based on manganese uptake by viable myocardium in the infarct core (IC), peri-infarct region (PIR) and remote myocardium (RM) using T1 mapping before and after MEMRI and assess their association with cardiac function and arrhythmogenesis. Methods: Fifteen female swine had a 60-minute balloon ischemia-reperfusion injury in the LAD. MRI (Signa 3T, GE Healthcare) and electrophysiological study (EPS) were performed 4 weeks later. MEMRI and delayed gadolinium-enhanced MRI (DEMRI) were acquired on LV short axis. The DEMRI positive total infarct area was subdivided into the regions of MEMRI-negative non-viable IC and MEMRI-positive viable PIR. T1 mapping was performed to evaluate native T1, post-MEMRI T1, and delta R1 (R1post -R1pre, where R1 equals 1/T1) of each territory. Their correlation with LV function and EPS data was assessed. Results: PIR was characterized by intermediate native T1 (1530.5 ± 75.2 ms) compared to IC (1634.7 ± 88.4 ms, p = 0.001) and RM (1406.4 ± 37.9 ms, p < 0.0001). Lower post-MEMRI T1 of PIR (1136.3 ± 99.6 ms) than IC (1262.6 ± 126.8 ms, p = 0.005) and higher delta R1 (0.23 ± 0.08 s −1 ) of PIR than IC (0.18 ± 0.09 s −1, p = 0.04) indicated higher myocardial manganese uptake of PIR compared to IC. Post-MEMRI T1 ( r = −0.57, p = 0.02) and delta R1 ( r = 0.51, p = 0.04) of PIR correlated significantly with LVEF. Conclusions: PIR is characterized by higher manganese uptake compared to the infarct core. In the subacute phase post-IR, PIR viability measured by post-MEMRI T1 correlates with cardiac function. Graphical abstract: Unlabelled Image Highlights: Myocardial viability of the peri-infarct region can be measured by manganese uptake. The peri-infarct region has distinct T1 values pre- and post- manganese injection. Quantitative manganese signals of the peri-infarct region correlates with LV function.